Changing Retirement Policies. Current Issues in Higher Education, 1978 - American Association for Higher Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1978)
Changes in federal law regarding mandatory retirement policy, while not directly covering higher education until 1982, will have much earlier educational and financial impacts on colleges and universities. Educational decision-makers will modify their behavior in such areas as hiring and tenure decisions, retirement decisions, and faculty pay decisions. The three papers presented here discuss the outcomes of this situation. "A Research Perspective on Mandatory Retirement," by Thomas M. Corwin, is based on a survey of institutions that was designed to discover the impact of raising retirement ages on educational institutions, and the effects on the employment prospects of new doctorate holders. "Implications of Mandatory Retirement Legislation for Institutions of Higher Education," by Peggy Heim, considers the impact of new retirement legislation on institutions, with emphasis on financial considerations. Included are analyses of both the direct and indirect effects, taking account of the attitudes and actions of both faculty members and administrators. "Faculty Attitudes Toward Early Retirement," by David D. Palmer and Carl V. Patton, is based on two independently conducted studies of faculty attitudes toward early retirement. One study focused on attitudes of existing faculty and the other on attitudes of those who recently took advantage of incentive early retirement programs. (Author/MSE)
Availability: American Association for Higher Education, Suite 780, One Dupont Circle, Washington, DC 20036 ($2.00).
ERIC Note: Papers presented at the Annual Meeting of the American Association for Higher Education (Chicago, IL, March 1978).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Attitudes; College Administration; College Faculty; Decision Making; Doctoral Degrees; Educational Economics; Employment Practices; Federal Legislation; Higher Education; Incentives; Mandatory Retirement; National Surveys; Retirement Benefits; Teacher Attitudes; Teacher Retirement; Early Retirement; Opinion Papers; Collected Works, Proceedings; Reports, Research